Entre a criação e a exposição: o museu como ateliê do artista. Breve introdução ao tema - Teresa Azevedo (Midas: Museus e Estudos Interdisciplinares)
This paper is a step towards understanding the current concept of the artist’s studio considered in its expanded field, exploring preliminary ideas for the writer’s ongoing investigation. Although in the early 1970s, artists such as Daniel Buren or Robert Smithson declared the ‘extinction’ of the studio, thus promoting a creative process with place as an intrinsic part of the work, resulting in what would later be known as the post-studio era, I will argue that the studio, if understood as ‘a space and a condition’ is always present in the genesis and development of the creative process, reflecting its inherent tensions, advances and regressions. With the expansion of this concept of the artist’s studio, its models in contemporary art production were also widened, allowing for new relations and dynamics with other devices from within or outside the art world. For many contemporary artists, the museum is an element of continuity from the studio, many times the preferred space for the creation of new artworks. It’s precisely this perspetive of the museum as artist’s studio that this paper intends to consider, introducing recent studies on the subject as well as recent examples. I thereby intend to suggest possible avenues for a future discussion regarding the contribution of a transdisciplinary study of the artist’s studio to a greater knowledge of contemporary artistic production, as well as its reception, documentation or musealization.